THE IMPACT OF POLYCYSTIC OVARY SYNDROME (PCOS) ON THE MENTAL HEALTH OF PATIENTS – A CROSS-SECTIONAL STUDY WITH EXTENDED CLINICAL AND PUBLIC HEALTH IMPLICATIONS - Julia Konat; Jan Noskowicz; Jan Urban; Wiktor Doroszuk; Dawid Sewruk; Katarzyna Sikora; Mathias Spitaleri; Arleta Gieniec; Filip Kieloch; Agnieszka Fitas (International Journal of Innovative Technologies in Social Science, 2025)
Background: Polycystic Ovary Syndrome (PCOS) is a common endocrine disorder affecting up to 10% of reproductive-aged women. Beyond reproductive symptoms, PCOS is increasingly associated with mental health challenges, including depression, anxiety, and stress, often overlooked in routine care. Aim: This study assessed the prevalence and severity of psychological symptoms in women with PCOS and identified clinical and behavioral predictors of poor outcomes, with emphasis on modifiable lifestyle factors. Methods: A cross-sectional study was conducted among 200 women aged 18–40 diagnosed with PCOS by Rotterdam criteria. Participants completed the Depression, Anxiety and Stress Scale-21 (DASS-21) and a survey on sleep, physical activity, nutrition, and social support. Clinical indicators included BMI, menstrual regularity, hirsutism, and acne. Pearson correlations and regression models were used to analyze associations. Results: Moderate to severe depression affected 62% of participants, elevated anxiety 54%, and high stress 38%. Higher BMI, irregular cycles, and hirsutism were strongly correlated with worse psychological scores. Protective factors included regular physical activity, sufficient sleep, and positive body image. Regression analyses confirmed both clinical and behavioral predictors were significant (p < 0.05). Conclusions: Women with PCOS experience a substantial psychological burden. Routine care should integrate mental health screening and multidisciplinary management. Lifestyle interventions focusing on exercise, sleep, and body image may significantly improve emotional well-being and overall quality of life.